Diversity and the Eurosphere. (August 2014) - Kivisto, Peter
This paper offers reflections on the Eurosphere's proper object domain. It does so by reflecting on two interrelated questions: (1) what is the European public sphere?; and (2) how does diversity shape the character of the European public sphere?